Prevalence of extended spectrum B lactamase producing E.coli and Klebsiella SPP isolated in a tertiary care hospital, Gujarat - Dr. Hitesh Assudani; Dr. Jigar Gusani (Tropical Journal of Pathology and Microbiology, 2019)
Background: Antibiotic resistance among gram negative bacilli is a rapidly expanding problem due to the organism’s ability to mutate and to acquire the transmit plasmid and other genetic elements encoding resistance genes.Objective: This study was conducted to know the prevalence of ESBLs in E. coli and Klebsiella spp. isolates obtained from clinical samples. Material and Methods: A detailed history was taken and Performa was filled for each patient documenting age, sex, history of illness was obtained. Study was conducted at microbiology Department, Gujarat Adani Institute of Medial Sciences, Bhuj from May 2014 to Dec 2015. Total 2500 clinical samples like Urine, Sputum, Blood, Pus, CSF, Pleural fluid were collected in sterile containers. Samples from which E.coli and Klebsiella spp were isolated were considered for this study. Detection of ESBL was done as per CLSI guidelines.Results: Total 2500 clinical samples were tested for culture and sensitivity during August 2015 to July 2017. Out of this 500 samples showed growth of E. coli and Klebsiella spp. Among 500 isolates coli had 268 and from them 189 were ESBL positive. Similarly 232 were isolates from Klebsiella spp and among them 185 were positives for ESBL.Conclusion: In the present study, ESBL prevalence was 49.99% (E. coli = 50.53% and K. pneumoniae = 49.46%). A moderately high prevalence of ESBL producing E. coli and K. pneumoniae was observed and confirmed in the urine, sputum, pus, CSF and Blood. A strict hospital infection control policy and a prudent anti-microbials use regimens are to be adopted by the physicians.